THE EFFECTIVENESS OF INTERNAL AUDIT IN IMPROVING GOOD UNIVERSITY GOVERNANCE AT THE UNIVERSITY OF NORTH SUMATERA - Nasution, Hasnah Juniarni; Deliana, Deliana; Napitupulu, Ilham Hidayah (UPT Publikasi Ilmiah UNISBA, 2024)
The effectiveness of internal audit is needed to realize good university governance because in internal audit there is a mechanism to ensure that the management carried out by the institution is effective and in accordance with good governance. Good governanceis the foundation for creating a healthy institution and one of the keys to successful institutional management. Knowing the level of internal audit effectiveness, the implementation of university governance, and how internal audit effectiveness realizes the implementation of good university governance at the University of North Sumatera is the purpose of this research. This research uses a descriptive quantitative method with data collection techniques by distributing questionnaires and interviewing key informants. The data analysis technique used is descriptive analysis. The results showed that the effectiveness of internal audit and the implementation of university governance were in the effective or good category. If internal audits are effective, then university governance will be good. University governance can run well if internal audits are effective. Keywords : Internal audit effectiveness, Good university governance, University governance.